Night relics : a ghost story - Blaylock, James P. (New York: Berkley Books, 1994)
"A ghost story with the fever of dream logic of nightmare ... -- Eerie and terrifying -- A powerful story full of creepy moments --
English
Keywords: Fiction; A ghost story - fiction; Eerie- fiction; Terrifying -fiction.; Mystery - fiction